Something, Someday - Gorman, Amanda, 1998-; Robinson, Christian (New York : Viking, 2023)
Reveals how even the smallest gesture can have a lasting impact on the world's biggest problems.
new kids book 2023 fall.
Ages 4-8.
Grades K-1.
Keywords: Kindness -- Fiction; Helpfulness -- Fiction; Hope -- Fiction; Picture books for children; Picture books